2017
DOI: 10.1016/j.intfin.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent lead-lag relationship between the onshore and offshore Renminbi exchange rates

Abstract: We employ the thermal optimal path method to explore both the long-term and short-term interaction patterns between the onshore CNY and offshore CNH exchange rates (2012)(2013)(2014)(2015). For the daily data, the CNY and CNH exchange rates show a weak alternate lead-lag structure in most of the time periods. When CNY and CNH display a large disparity, the lead-lag relationship is uncertain and depends on the prevailing market factors. The minute-scale interaction pattern between the CNY and CNH exchange rates… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…Therefore, the offshore Renminbi (CNH/USD), quoted also by the Swiss forex bank Dukascopy from July 2, 2012 is here used. There, in addition, already also exist quantitative studies documenting that the three RMB markets, including the third one existing, offshore RMB non-deliverable forward market (NDF market), largely cointegrate after the reform (Xu et al, 2017;Ruan et al, 2019). Collection of the corresponding charts illustrating price p(t) changes of all the instruments considered in the present study is depicted in Fig.…”
Section: Data Specificationmentioning
confidence: 94%
“…Therefore, the offshore Renminbi (CNH/USD), quoted also by the Swiss forex bank Dukascopy from July 2, 2012 is here used. There, in addition, already also exist quantitative studies documenting that the three RMB markets, including the third one existing, offshore RMB non-deliverable forward market (NDF market), largely cointegrate after the reform (Xu et al, 2017;Ruan et al, 2019). Collection of the corresponding charts illustrating price p(t) changes of all the instruments considered in the present study is depicted in Fig.…”
Section: Data Specificationmentioning
confidence: 94%
“…According to (18), it can be obviously found that the lead-lag relationship between two time series X(t) and Y(t) changes in the five different time periods. There is zero time lag between X and Y in the first and fifth time periods.…”
Section: Comparison On Multiple-change-of-regime In Time Lagmentioning
confidence: 99%
“…The time series X is assumed to be the first-order AR process (17) and η is a Gaussian white noise with mean of 0 and variance of 0.1. Similarly to 2.3.1, by using existing TOP method and adjusted TOP method, we conduct the simulation tests on detection of lead-lag relationship between X and Y descried as (18) and present the results in Figure 2. Figure 2 shows the transverse trajectory 〈 ( )〉 as a function of the time step i based on the existing TOP method and adjusted TOP method.…”
Section: Comparison On Multiple-change-of-regime In Time Lagmentioning
confidence: 99%
See 1 more Smart Citation
“…To proxy for RMB foreign exchange rates, we employ the on-shore RMB-USD exchange spot rates (RU) and the on-shore RMB-JPY exchange spot rates (RY). For robustness check purpose, we also select the off-shore exchange spot rates between RMB and USD (OFFRU) and between RMB and JPY (OFFRY), because the existing literature shows evidence that the off-shore RMB exchange rates are much dependent on the on-shore rates (Funke et al 2015;Ren et al 2018;Xie et al 2017;Xu et al 2017). For stock market indices, we use the Tokyo Stock Exchange Price Index (TPX) and the Nihon Keizai Shimbun 225 (NIK) in Japan, and the Shanghai Composite Stock Market Index (SHCI) and the Shenzhen Composite Stock Market Index (SZCI) in China.…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%